Role of histamine as a toxic mediator in the pathogenesis of vitiligo - Salil Kumar Panja; Biman Bhattacharya; Sitesh Chandra Lahiri (Wolters Kluwer Medknow Publications, 2013)
Background: The precise cause of vitiligo is still unclear. Multiple theories have been proposed, including genetic, autoimmune, neural, and biochemical mechanisms. An immune mediated pathogenesis is indeed the most popular theory. The autoimmune hypothesis considers the role of toxic mediator that might cause an injury to the melanocytes with the release of an antigenic substance and subsequent autoimmunization. Aims: This study performed over a period of 10 years (February 1975 to June 1985) aims at exploring the role that histamine might play in the pathogenesis of vitiligo. Materials and Methods: Fifty patients with a particular type of vitiligo characterized by faint white patches occurring with significant pruritus and a history of atopy were selected and blood histamine levels were determined by Bio-Assay method. Results: Blood histamine values of patients with vitiligo of short duration and with pruritus were significantly increased in comparison with values of matched controls. Conclusion: Histamine appears to play a significant role in the pathogenesis of a particular type of vitiligo characterized by faint hypopigmented patches with significant itching.